E-Learning System For Physical Education In IAIN Salatiga Using Google Classroom - Fatkhur Rozi; Mega Widya Putri; M. Riski Adi Wijaya (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
This study aims to analyze the process of lecturing the theory and practice of physical education at the Salatiga State Islamic Institute (IAIN Salatiga) using the google clasroom media. The method used is qualitative with a phenomenological approach and case study design to examine in depth the aspects that influence the use of google classroom media in the physical education learning. The results of this study are the physical education e-learning using google classroom at IAIN Salatiga can be used as a solution to the limitations of theoretical and practical in the physical education learning. Furthermore, it makes it easier for lecturers to deliver physical education material and makes it easier for students to learn physical education material. Internet signal access is a major obstacle in e-leraning physical education using google classroom at IAIN Salatiga.